(untitled) (Zoological Records and Reviews, 2025)
Habitat restoration – the deliberate intervention to assist recovery of a degraded or destroyed ecosystem toward a reference condition – has emerged as a central strategy for biodiversity conservation and is now mandated at scale through the EU Nature Restoration Law (2024/1991) and the Kunming-Montreal Global Biodiversity Framework 30x30 and restoration targets. This review synthesises evidence from 284 peer-reviewed studies published between 2000 and 2024 on faunal recovery following habitat restoration across European terrestrial and freshwater ecosystems, covering six restoration types (riparian, peatland, heathland, grassland, woodland, and river floodplain) and five vertebrate and invertebrate groups. Meta-analysis of 148 studies providing quantitative recovery data confirms that restoration increases faunal diversity by a mean of 34.8% (95% CI: 28.4-41.2%) relative to degraded controls, but recovery to reference condition levels takes 8-42 years depending on taxon and restoration type. Recovery rates are highest for mobile generalists (breeding birds, butterflies; mean 85.4% of reference richness at 10 years) and slowest for sedentary specialists (freshwater molluscs, amphibians; mean 42.4% at 10 years). The single most important predictor of restoration success across all studies was donor-population connectivity – access to source populations for recolonisation – which accounted for 38.4% of variance in recovery rate (partial R2 in meta-regression). Management intensity post-restoration (active vegetation management, predator control, water level management) was the second most important predictor (partial R2 = 0.24). These findings provide an evidence synthesis for prioritising restoration investment and design under EU Nature Restoration Law national planning obligations.